2015
DOI: 10.1002/cplu.201500134
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks via Emissive Metal‐Carboxylate Zwitterion Intermediates

Abstract: What is the most significant result of this study?We demonstrated the isolation of emissive zwitterions that are intermediates in the metal-organic framework assembly process. These simple zwitterions are structurally interesting (for another paper on the isolation of transition-metal-based zwitterions, see: RSC Adv. 2015, 5,4 2978). We also showed, for the first time, that pyridine alcohol/carboxylate hybrid ligands are suitable for construction of apotentially diverse class of porous materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 77 publications
2
15
0
Order By: Relevance
“…The Brunauer-Emmett-Teller (BET) surface area of MOF 1 can be roughly estimated based on the CO 2 adsorption data in the linear range (P/P 0 < 0.07) to be 155 m 2 g −1 . MOF 1 also adsorbs up to 58.61 cm 3 g −1 CO 2 (2.63 mmol g −1 , 11.6 wt % at standard temperature and pressure, STP), comparable with the respective data found for the 3D MOFs of [Zn( iso -hmn)] (1.63 mmol g −1 ; 7.23 wt % at STP; iso -hmn = 2-(hydroxymethyl)isonicotinate) [ 81 ], [Cd 3 (BTB) 2 (bpe)(H 2 O) 2 ] (3.94 mmol g −1 ; 17.3 wt % at STP; bpe = trans -1,2-bis(4-pyridyl)ethylene) [ 45 ], and Mn(2,6-ndc) (3.0 mmol g −1 ; 13.0 wt % at STP; ndc = 2,6-naphthalenedicarboxylate) [ 86 ]. It is also notable that the activated samples of MOF 1 exhibit nearly no CO 2 uptake at 273 K and 298 K ( Figure 4 ).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The Brunauer-Emmett-Teller (BET) surface area of MOF 1 can be roughly estimated based on the CO 2 adsorption data in the linear range (P/P 0 < 0.07) to be 155 m 2 g −1 . MOF 1 also adsorbs up to 58.61 cm 3 g −1 CO 2 (2.63 mmol g −1 , 11.6 wt % at standard temperature and pressure, STP), comparable with the respective data found for the 3D MOFs of [Zn( iso -hmn)] (1.63 mmol g −1 ; 7.23 wt % at STP; iso -hmn = 2-(hydroxymethyl)isonicotinate) [ 81 ], [Cd 3 (BTB) 2 (bpe)(H 2 O) 2 ] (3.94 mmol g −1 ; 17.3 wt % at STP; bpe = trans -1,2-bis(4-pyridyl)ethylene) [ 45 ], and Mn(2,6-ndc) (3.0 mmol g −1 ; 13.0 wt % at STP; ndc = 2,6-naphthalenedicarboxylate) [ 86 ]. It is also notable that the activated samples of MOF 1 exhibit nearly no CO 2 uptake at 273 K and 298 K ( Figure 4 ).…”
Section: Resultssupporting
confidence: 79%
“…In our case, we found that the TGA of the activated sample exhibits similar scaffold decomposition temperature as that of the as-synthesized ( Figure 1 ), but its PXRD pattern becomes amorphous ( Figure S2 ), suggesting some collapse of the crystal under the activation condition and may ultimately lead to the reduction of the pore size to exclude the N 2 uptake. MOF 1 exhibited a type I CO 2 adsorption profile with steep uptake in the low-pressure region, typical of a microporous material with open channels in the degassed phase [ 45 , 81 , 82 , 83 ]. The CO 2 adsorption isotherm for MOF 1 exhibits a negligible hysteresis upon desorption, an indication of the scaffold rigidity.…”
Section: Resultsmentioning
confidence: 99%
“…The CO 2 adsorption capacities were 73.2 cm 3 g −1 ( 1 a ), 32.5 cm 3 g −1 ( 1 b ), 24.8 cm 3 g −1 ( 2 a ), and 57.8 cm 3 g −1 ( 2 b ), corresponding to 3.3 mmol g −1 and 14.5 wt % at STP ( 1 a ), 1.4 mmol g −1 and 6.4 wt % at STP ( 1 b ), 1.1 mmol g −1 and 4.9 wt % at STP ( 2 a ), and 2.6 mmol g −1 and 11.4 wt % at STP ( 2 b ). These values are comparable to similar MOFs tested under equivalent experimental conditions, including [Cd 3 (BTB) 2 (Bipy)(H 2 O) 2 ] ⋅ x Sol (0.5 mmol g −1 , 2.0 wt % at STP), [Zn( iso ‐hmn)] (1.63 mmol g −1 ; 7.23 wt % at STP; iso ‐hmn=2‐(hydroxymethyl)isonicotinate) …”
Section: Resultssupporting
confidence: 78%
“…Our previous trial of the solvothermal reaction of Cd(NO 3 ) 2 ∙4H 2 O and H 3 BTB in a DEF/H 2 O/HNO 3 mixed solvent with CaSO 4 yielded a 3D anionic MOF of [Et 2 NH 2 ] 2 [Cd 5 (BTB) 4 (DEF) 2 ]∙4.75DEF featuring a zigzag-shaped Cd 5 cluster SBU [ 65 ]. The [Et 2 NH 2 ] + cations likely arose from the acid-catalyzed hydrolysis of DEF [ 67 , 68 , 69 , 70 ], and subsequently served as a template for the framework formation. In the present work, we employed CaO as a replacement of CaSO 4 to consume part of the acid, and the new neutral 3D MOF 1 was thus obtained in a high yield of 87%.…”
Section: Resultsmentioning
confidence: 99%
“…The motivation for introducing Ca 2+ into a Cd 2+ /H 3 BTB assembly originated from our quest to incorporate Ca 2+ into the linear Cd 3 -based two-dimensional (2D) MOF of [Cd 3 (BTB) 2 (DEF) 4 ]•2(DEF) 0.5 [62,63], as we and others have demonstrated that the heterometallic combinations of Cd/Zn, Cd/Co, and Zn/Co are readily tolerated in linear trimetallic cluster SBUs [26,66] [65]. The [Et 2 NH 2 ] + cations likely arose from the acid-catalyzed hydrolysis of DEF [67][68][69][70], and subsequently served as a template for the framework formation. In the present work, we employed CaO as a replacement of CaSO 4 to consume part of the acid, and the new neutral 3D MOF 1 was thus obtained in a high yield of 87%.…”
Section: Synthesis and Materials Characterization Of Mofmentioning
confidence: 94%